PERHITUNGAN PRODUKSI ALAT BERAT PADA PEKERJAAN JALAN TALISAYAN KABUPATEN BERAU - Yulfadli, Zony (KURVA S, 2016)
ABSTRACTRoad Work development projects Talisayan District Berau is one of the large projects with form uneven ground surface, where the implementation of maturation is dominated by the use of tools weight. Problems that arise in the use of heavy equipment is operating and the combination tool - heavy equipment that is wrong with the condition of the tool. The decline in productivity of the machine is also caused by the condition equipment, operator skill, the cycle time, the type of material, the working conditions, governance and weather conditions.                 So that the required selection and determination of the composition of the right tools so that heavy equipment can be a defender Gov optimally and the work can be completed on time at a cost efficient as possible. This study is the method of calculation of the production capacity of the actual machine. The analysis conducted ie the calculation of productivity calculations each - each machine is used, by determining cycle time tool, determining factor correction tools, persiklus production calculations, hourly production, production per day, the amount of equipment rental price per hour, the cost and time required for the tool works,determine the unit price and the determination of the exact composition of heavy equipment. The magnitude of the productivity of the machine with the most cost and time effective and efficient.Use composition tool alternative to - 3 ie 8 units of excavators 609.6384 m3 / hour, 5 units of bulldozer 571.2079 m3 / hour, 5 units of vibration roller 469.665 m3 / h, 22 units of dump trucks 612.1302 m3 / h, 1 unit motor grader 987.84 m2 / h and 5 units wheel loader 446.135 m3 / h with total cost and total execution time Rp.37.547.895.680 1760 hours or 220 day. Key words:  Equipment, Productivity, Cost, Duration